2019
DOI: 10.1186/s13020-019-0254-9
|View full text |Cite|
|
Sign up to set email alerts
|

Identifying the active components of Baihe–Zhimu decoction that ameliorate depressive disease by an effective integrated strategy: a systemic pharmacokinetics study combined with classical depression model tests

Abstract: Background Modern pharmacological studies have demonstrated that Baihe–Zhimu decoction (BZD) has antidepressant effects. However, the complex composition and lack of clear evaluation standards for BZD make it less likely to be understood and accepted than evidence-based active natural compounds. Methods In this study, an effective method for the identification of antidepressant components was demonstrated and applied to BZD. The firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…The Strength of this study included the following aspects: (1) This study was a multicenter, randomized, double-blind placebo-controlled trial with a good design and relatively large sample size. (2) the composition of the Zishen Pingchan recipe was modified by adding two traditional Chinese medicines, Zhimu and Baihe because some studies showed that Zhimu-baihe Decoction significantly improves the symptoms of depression in PD patients [34,35]. This change may increase the efficacy of ZPG and exert more benefits in dPD patients.…”
Section: Discussionmentioning
confidence: 99%
“…The Strength of this study included the following aspects: (1) This study was a multicenter, randomized, double-blind placebo-controlled trial with a good design and relatively large sample size. (2) the composition of the Zishen Pingchan recipe was modified by adding two traditional Chinese medicines, Zhimu and Baihe because some studies showed that Zhimu-baihe Decoction significantly improves the symptoms of depression in PD patients [34,35]. This change may increase the efficacy of ZPG and exert more benefits in dPD patients.…”
Section: Discussionmentioning
confidence: 99%
“…40 Concordant with our results, Baihe-Zhimu decoction was earlier reported to reduce immobility time in the FST and TST, thus exerting antidepressant effects. 9 Another study indicated that Baihe-Dihuang powder was able to improve the pathological changes evident in the thymus and spleen of chronic stress depression animal model. 18 The current data also demonstrated that Baihe extracts curtailed microglial apoptosis, activation, and inflammatory mediator release in vivo and in vitro.…”
Section: ■ Discussionmentioning
confidence: 99%
“…8 The active components of the Baihe-Zhimu decoction are also found to ameliorate depressive disease. 9 These findings suggest that Baihe extracts may possess the capacity to alleviate depressive diseases, which warrants investigation of the underpinning mechanisms involved. As a family of pleiotropic transcription factors, MYC proteins orchestrate multiple cellular functions, including proliferation, growth, metabolism, and regulation of tissue remodeling and regeneration.…”
Section: ■ Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Change the composition of Lily Bulb and Rehmannia Decoction and add Anemarrhena asphodeloides Bge, then Lily Bulb and Rehmannia Decoction became Lily Bulb and Rhizoma Anemarrhena Decoction. Anemarrhenae was cold in TCM theory, and it would turn the efficacy of decoction colder [ 48 ]. By adding Anemarrhena asphodeloides Bge., the heat-clearing function of the decoction could be strengthened, making it more suitable for those who were already diagnosed as internal heat and Yin deficiency syndrome with more heat.…”
Section: Therapeutic Methods Proposed By Traditional Chinese Medicinementioning
confidence: 99%